Biological and residual activity of candidate larvicide formulation, SumiLarv 2MR, against an exotic invasive mosquito Anopheles stephensi Liston, 1901 (Diptera: Culicidae) in Ethiopia - Delenasaw Yewhalaw; Ebisa Erena; Teshome Degefa; Yehenew G. Kifle; Endalew Zemene; Eba Alemayehu Simma (Scientific Reports)
Abstract The study evaluated the efficacy and residual activity of SumiLarv 2MR, SumiLarv 0.5G, and Abate 1SG (used as a positive control) against Anopheles stephensi larvae in Awash Subath Kilo, Afar Regional State, Ethiopia, using a semi-field experimental setup. Plastic containers with capacities of 100L and 250L were used to assess the residual efficacy of SumiLarv 2MR. Specifically, four 100L containers were each treated with one disc of SumiLarv 2MR, compared to two untreated controls. Similarly, four 250L containers received one disc each, with two untreated controls. Additionally, eight 250L containers were treated with a half-dose to match one disc per 500L, alongside four untreated controls. For SumiLarv 0.5G and Abate 1SG, four 100L containers were treated with each larvicide, with two untreated controls for each. Each container received 20–25 third and fourth instar An. stephensi larvae. Observations of adult emergence were conducted until all pupae either emerged or died. Results showed that SumiLarv 2MR demonstrated a nine-month residual efficacy, SumiLarv 0.5G provided seven weeks of efficacy, and Abate 1SG showed a five-week efficacy. Additionally, SumiLarv 2MR discs retained nearly 50% of their initial pyriproxyfen content after nine months, suggesting potential for extended residual activity. This study highlights the long-term effectiveness of SumiLarv 2MR’s as a larvicide against An. stephensi in Ethiopia.